Research on the Evaluation Model of Automotive Talents Based on Factor Analysis Method - Shi, Yingqi; Guo, Chao (International Journal of Computer Science and Information Technology, 2024)
With the rapid development of the automotive industry, the demand for high-quality talents is increasing day by day. This article uses factor analysis method to construct an automotive talent evaluation model, aiming to help enterprises select and cultivate talents more effectively through the analysis of talent characteristics. The research results indicate that professional basic theories, professional technical skills, innovative thinking ability, project management skills, and market & industry development awareness are key factors affecting the identification evaluation of automotive talents.